Analisis Konseptual Organisasi Pembelajaran (Learning Organization) - Sartika, Ratu; Hayadi, Bambang Herawan (Peneliti.net, 2024)
In order to make changes or paradigm shifts to the current situation and conditions as well as efforts to overcome the challenges or obstacles found in an organization, it is necessary to have a strategy through the implementation of a learning organization in order to produce quality and professional performance. This study is a literature review from various resources. As for the results of this study, it can be perceived from various explanations of research that has been carried out by previous researchers